The lucky stone - Sammon, Stella; Paice, Margaret, 1920- (London : Methuen, 1969)
Quei, a young aboriginal girl, and her brother Bundjell leave their camp and travel to town so that Quei's lame leg can be cured. They have many new and strange experiences but Quei feels protected by her lucky stone.
Muir, M. A bibliography of Australian children's books
For children.
Keywords: Children with disabilities -- Australia -- Juvenile fiction; Charms -- Australia -- Juvenile fiction; Aboriginal Australians -- Juvenile fiction; Literature and stories - Juvenile; Hunting - Birds; Health services; Animals - Birds - Ducks / Geese; Australia, Northern -- Juvenile fiction; Georgina River (Qld Far West SF54); Queensland Far North West (Qld Far NW SE54); Adventure stories; Children's stories, Australian